Validating the Reliability and Validity of the Persian Version of the Mini-Manual Ability Classification System - azade riyahi; Nazila Akbarfahimi; nazanin sarlak; hosseinali Abdolrazaghi; zahra nobakht (Journal of Rehabilitation Sciences and Research, 2023)
Background:Cerebral Palsy (CP) describes a group of permanent disorders of the development and posture, causing activity limitation. More than half of the children with CP experience various upper extremity problems with varying severity. Considering the importance of knowing the ability of children under 4 years old the aim of this study was to determine prepare Persian version mini-Manual Ability Classification System (mini-MACS) and evaluating its validity and reliability.Methods In a methodological study, after translation procedures, the face validity, content validity, test–retest reliability and interrater reliability of the Persian version of mini-MACS were evaluated. In total, 100 parents of children with cerebral palsy, 12 occupational therapists and a researcher participated in the evaluation of the scale’s reliability. Fifty six boys and 44 girls with cerebral palsy with an average age of 33.21 (SD=11.37) month participated in the study.Results The overall results indicated that the words and sentences used in mini-MACS were simple, clear, understandable, relevant and necessary. The ICC for test–retest reliability for parents, occupational therapists and researchers were 0.955, 0.979 and 0.943, respectively. The interrater reliability coefficient between parents and occupational therapists was 0.939, between parents and researcher was 0.954, and between occupational therapists and researcher was 0.922.Conclusion:The Persian version of mini-MACS seems to be valid and reliable. This system could be used to evaluate children with cerebral palsy.